Identifikasi Sektor Unggulan di Kabupaten Konawe Selatan - Puspitaningsih, Andriani; Permana, Teguh; Djauhar, Asri (Multiverse: Open Multidisciplinary Journal, 2023)
This research delves into the identification of key sectors in South Konawe District, utilizing Location Quotient (LQ) analysis to focus on the base sector. The findings highlight three sectors with LQ values exceeding 1: (1) agriculture, forestry, and fisheries, (2) mining and quarrying, and (3) transportation and warehousing. These sectors emerge as leading contributors, underlining their pivotal role in the local economy. The results provide crucial insights for crafting effective regional development strategies and optimizing resource allocation. Moreover, the recognition of these leading sectors equips policymakers and stakeholders with a strategic framework for targeted interventions, fostering not only economic resilience but also sustainable growth in South Konawe District.